2007
DOI: 10.1161/01.hyp.0000253780.36691.4f
|View full text |Cite
|
Sign up to set email alerts
|

Aliskiren Reduces Blood Pressure and Suppresses Plasma Renin Activity in Combination With a Thiazide Diuretic, an Angiotensin-Converting Enzyme Inhibitor, or an Angiotensin Receptor Blocker

Abstract: Abstract-Thiazide diuretics, angiotensin-converting enzyme inhibitors, and angiotensin receptor blockers all cause reactive rises in plasma renin activity. We hypothesized that renin inhibition with aliskiren would prevent this reactive rise and also enhance blood pressure lowering. In 3 open-label studies in which blood pressure was assessed with ambulatory measurement, aliskiren was administered to patients with mild-to-moderate hypertension in combination with hydrochlorothiazide (nϭ23), ramipril (nϭ21), or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
119
0
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(133 citation statements)
references
References 35 publications
6
119
0
8
Order By: Relevance
“…Clinical studies showed that aliskiren lowers SBP and DBP both in younger and elderly hypertensive patients [40], and that greater antihypertensive effect is achieved when given aliskiren in combination with a thiazide diuretic, other blockers of the RAAS system, or a calcium antagonist [41]. The APOLLO trail (The Aliskiren Prevention of Later Life Outcomes) showed that the administration of the combination of aliskiren and hydrochlorothiazide or amlodipine, and used other background antihypertensive drugs (mean of 1.5 drugs), was associated with an anticipated SBP reduction of 10 mmHg and appeared to be safe in the elderly [42].…”
Section: Pharmacology Of Aliskirenmentioning
confidence: 99%
“…Clinical studies showed that aliskiren lowers SBP and DBP both in younger and elderly hypertensive patients [40], and that greater antihypertensive effect is achieved when given aliskiren in combination with a thiazide diuretic, other blockers of the RAAS system, or a calcium antagonist [41]. The APOLLO trail (The Aliskiren Prevention of Later Life Outcomes) showed that the administration of the combination of aliskiren and hydrochlorothiazide or amlodipine, and used other background antihypertensive drugs (mean of 1.5 drugs), was associated with an anticipated SBP reduction of 10 mmHg and appeared to be safe in the elderly [42].…”
Section: Pharmacology Of Aliskirenmentioning
confidence: 99%
“…[1][2][3] To date, several investigators have studied the association of pretreatment plasma renin activity (PRA) levels with ambulatory blood pressure (ABP) responses to ARBs in essential hypertension. [4][5][6] Recently, we showed that ABP reductions by telmisartan were significantly smaller in hypertensive patients with lower PRA levels than in those with higher PRA levels. 4 However, it is uncertain whether the same is true of all ARBs.…”
mentioning
confidence: 99%
“…These findings are well in agreement with our earlier observation regarding telmisartan, 4 and earlier observations by other investigators regarding losartan 5 and irbesartan. 6 Therefore, measurements of pretreatment PRA levels are thought to be useful to predict the ABPlowering effects of ARBs, irrespective of drugs, and should be performed routinely before the initiation of antihypertensive medication, especially in untreated and newly diagnosed patients with essential hypertension.…”
mentioning
confidence: 99%
See 2 more Smart Citations